Transcritical carbon dioxide heat pump cycle: Validation and comparison of one-dimensional models of ejector with independent data sets. (August 2022) - You, Cong; Michel, Benoit; Revellin, Rémi
Abstract: Two typical 1-D homogeneous equilibrium models from the literature (constant and variable pressure mixing models) were used to study the ejector expansion transcritical CO 2 heat pump cycle. A sensitivity analysis was performed to study the impact of the isentropic efficiency of the compressor and of each component of the ejector on the overall system performance. Two groups of independent experimental data from the literature were used to validate the two models. It was found that the cycle performance was more sensitive to the isentropic efficiency of the compressor than that of the individual components of the ejector. With appropriate input value of the compressor efficiency, both 1-D models accurately predicted the ejector outlet pressure and vapor quality. However, for the ejector entrainment ratio and cycle COP, the deviations were more than 50 %. These deviations can be significantly minimized to 10 % by eliminating the imbalance occurring in the system operation using a data post-processing method to correct the pseudo steady state in the real operation system. By comparing the simulation results of the two models, it has been shown that there is minor difference on the prediction accuracy. The research can serve as a practical reference for the operation of two-phase-flow ejector expansion transcritical heat pump cycle, and can also provide an insight and orientation for the subsequent optimization of 1-D ejector numerical models. Highlights: Two 1-D homogeneous equilibrium models of the ejector are experimental validated. Neglecting the pressure variation during the mixing has no significant impact. The liquid imbalance is a predominant source of the modeling deviation. An innovative data post-processing method is proposed. The system performance is more sensitive to the compressor isentropic efficiency.